FINANCING OF SCIENTIFIC WORK IN AGRICULTURAL UNIVERSITIES OF UKRAINE - Olesia TOTSKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this article is to analyze the commercialization of the results of scientific work of agricultural universities of Ukraine and the formation of their ratings according to these indicators. Data from the Ministry of Education and Science of Ukraine for the years 2018–2020 were used to achieve the goal. The research was carried out in three stages: analysis of absolute indicators of commercialization (amounts of earned funds based on the results of scientific work) using the ABC method; analysis of relative indicators of commercialization (amount of earned funds based on the results of scientific work per one scientific-pedagogical worker); formation of ratings of agricultural higher education institutions of Ukraine according to absolute and relative indicators of commercialization of scientific work. The following results were obtained: during the analyzed period, agricultural higher education institutions of Ukraine improved the overall effectiveness of scientific activity. In 2019, 7 higher education institutions, and in 2020, 11 higher education institutions increased the absolute financial indicators of their scientific work, compared to the previous year. In 2019, 8 higher educational institutions, and in 2020, 11 higher educational institutions increased the relative financial indicators of their scientific work, compared to the previous year. According to the rating of agricultural higher education institutions of Ukraine, four leaders were identified according to these indicators. It is expedient to study and implement their experience in attracting funds for financing scientific work in other 12 agricultural higher education institutions of Ukraine.